MONITORING COMMON BEAN DEVELOPMENT WITH DIFFERENT WATER AND NITROGEN LEVELS BY SPECTRAL PROPERTIES - Monteiro, Priscylla Ferraz CÃ¢mara; Angulo Filho, Rubens; Monteiro, Rodrigo OtÃ¡vio CÃ¢mara; Adami, Marcos; Moreira, MaurÃcio Alves (REVISTA DE AGRICULTURA, 2013)
The aims of this study were to determine the impact of different nitrogen rates and water levels on biophysical (Leaf area index â€“ LAI) and spectral parameters obtained with continuum removal (band depth and area) of bean crop and to determine the growth stage that spectral parameters best correlated with LAI. Absorption band, positioned at 665 nm, was analyzed in depth and width. Field canopy reflectance measurements were acquired at six bean growth stages over 48 plots with four water levels (179.5; 256.5; 357.5 and 406.2 mm), three nitrogen rates (0; 80 and 160 kg haâ€“1) and four replicates. The N had no effect on either absorption band area (AB) or the absorption band depth (PB) of the absorption band centered at 665 nm (chlorophyll) for the all growth stages.Â On the other hand, the irrigation level significantly affected these spectral parameters in most growth stages. The best correlations between LAI and absorption band parameters were observed at R6 stage.